Pain and measles, mumps, and rubella vaccination. Issue 3 (March 1991) - Lyons, R; Howell, F
Abstract : Seventy-seven children (mean age 44.2 months) were entered in a randomised double blind study to find out if two commonly used measles, mumps, and rubella (MMR) vaccines (Pluserix and MMR II) caused pain on injection. Pain was judged by the amount of crying. Infants given MMR II were 2.31 times more likely to cry than those given Pluserix.